Switchgrass nitrogen fertility response and nutrient cycling in a hay system. (15th April 2020) - Ashworth, A.J.; Moore, P.A.; King, R.; Pote, D.H.; Douglas, J.L.; Jacobs, A.A.
Abstract: Nitrogen (N) requirements for switchgrass ( Panicum virgatum L.) forage production in the Mid‐south are largely unknown. This study determined switchgrass forage yield, quality, N removal, and soil fertility response in a two‐forage harvest (pre‐anthesis) system after split applications of 0, 84, 168, 252, and 336 kg N ha –1 yr –1 from 2014 to 2016. Controls were represented by no fertilizer and a 0 N rate with supplemental P, K, Mg, and S. For all experimental years, yield did not benefit from supplemental P, K, Mg, and S, suggesting N was the limiting nutrient. Yield also did not differ between the 252 and the 336 kg N ha –1 yr –1 rates (9.2 and 9.4 Mg ha –1, respectively), indicating no further growth beyond the 252 kg N ha –1 threshold in a two‐cut forage system. At greater N fertility rates (336 kg N ha –1 ), the majority of the soil nutrient concentrations were reduced compared with the 252 kg N ha –1 rate, owing to greater nutrient removal in harvested plant tissue. Tissue N removal was greatest for the highest N application, albeit not different from the 252 kg N ha –1 rate; N use efficiency had an inverse relationship with N removal, peaking during the lowest N application (84 kg N ha –1 ). Forage quality varied, but, in general, digestibility improved under greater N fertility. Quantifying trends in forage yield and quality based on N fertility are useful for predicting break‐even prices per fertilizer response.